Evaluation of Oxytocin Level and Its Relationship With Oxidant-Antioxidant Status in Women With Polycystic Ovarian Syndrome: Evaluasi Tingkat Oksitosin dan Hubungannya dengan Status Oksidan-Antioksidan pada Wanita dengan Sindrom Ovarium Polikistik (SOPK) - Rawa Auda Hussein; Izdihar Nasaif Ali; Sarah Ashour Sayer (Academia Open, 2023)
Polycystic Ovarian Syndrome (PCOS) is a prevalent endocrine disorder associated with infertility in a substantial number of women globally. This study aimed to investigate the potential role of oxytocin (OXT) in PCOS pathogenesis and its implications for oxidative stress. A cohort of 120 females, comprising 60 PCOS patients and 60 healthy controls, aged between 25 and 31, was examined. Serum concentrations of OXT, superoxide dismutase (SOD), and myeloperoxidase (MPO) were measured. The results revealed significantly decreased OXT levels in PCOS patients compared to controls (p<0.001). Additionally, PCOS patients exhibited elevated MPO levels and reduced SOD levels, suggesting increased oxidative stress. Furthermore, a positive correlation between OXT and SOD and a negative correlation between OXT and MPO were observed within the PCOS group. These findings highlight the potential of OXT as a diagnostic tool and predictor of ovarian response and treatment success in PCOS, emphasizing the need to target oxytocin for mitigating oxidative stress in this complex endocrine disorder. Highlights: Oxytocin Deficiency: This study identifies significantly reduced oxytocin levels in PCOS patients, shedding light on its potential role in the disorder's pathogenesis. Oxidative Stress Imbalance: PCOS patients displayed an imbalance in oxidative stress markers, with elevated myeloperoxidase and reduced superoxide dismutase levels, indicating increased oxidative stress. Diagnostic and Therapeutic Implications: Oxytocin emerges as a promising diagnostic tool and predictor of ovarian response and treatment success in PCOS, emphasizing its potential as a therapeutic target to mitigate oxidative stress in this complex endocrine disorder. Keywords: PCOS,Oxytocin,Oxidative Stress,Infertility,Diagnostic Tool